2019
DOI: 10.1021/acs.molpharmaceut.9b00308
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonists and Strategies To Improve Their Efficiency

Abstract: Type 2 diabetes mellitus (T2DM) is increasing in global prevalence and is associated with serious health problems (e.g., cardiovascular disease). Various treatment options are available for T2DM, including the incretin hormone glucagon-like peptide-1 (GLP-1). GLP-1 is a therapeutic peptide secreted from the intestines following food intake, which stimulates the secretion of insulin from the pancreas. The native GLP-1 has a very short plasma half-life, owning to renal clearance and degradation by the enzyme dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 246 publications
0
61
0
2
Order By: Relevance
“…In the present study, PEG was used as a non-toxic polymer [26]. It is used for different purposes due to its aqueous solubility, low immunogenicity, and antigenicity and proper excretion kinetics [26,27].…”
Section: Preparation Of Nanoparticlesmentioning
confidence: 99%
“…In the present study, PEG was used as a non-toxic polymer [26]. It is used for different purposes due to its aqueous solubility, low immunogenicity, and antigenicity and proper excretion kinetics [26,27].…”
Section: Preparation Of Nanoparticlesmentioning
confidence: 99%
“…Diabetes is a complex and chronic disease that affects many organs of the body. It increases the risk of various disorders, such as retinopathy, neuropathy, nephropathy, and cardiovascular disease (Alavi, et al., 2019; Preguiça et al., 2020). These disorders are a remarkable cause of increased morbidity and mortality among diabetic people (Eid et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…42 Results of previous studies also demonstrated that PEGylation of liposomes caused an increase in the biological half-life of the encapsulated drug and as a result an increase in drug efficacy. 43,44 In addition, DSPE-PEG-Mal linker was used to conjugate thiolated OX26 to the surface of liposomes as well. Maleimide (Mal) reacts rapidly and efficiently with the thiol group.…”
Section: Discussionmentioning
confidence: 99%